THE RELATIONSHIP BETWEEN ACADEMIC FRAUDS WITH UNETHICAL ATTITUDE AND ACCOUNTING FRAUD - Laurensia Tjoanda; Pepie Diptyana (STIE Perbanas Surabaya, 2013)
The attitude of being dishonest is not only done by the practitioner or an accountant, but it isalso preceded by a fraud committed by students in formal education. This unethical behaviorwould arise when the accountants violate the professional code of ethics established by theAccountants Association in Indonesia (IAI). This study aims to analyze the relationships ofattitudes toward academic dishonesty attitude toward unethical behavior and attitudes towardaccounting fraud likelihood from public accountants perspective. Vignette used to collectdata with the population of registered public accountants in IAPI. The sample covers 43public accountants who have been participating in the Congress IAI XI in Jakarta, and publicaccountants in Surabaya. It was found out that there is significant correlation betweenattitudes with academic dishonesty and attitude with unethical behavior towards attitudes ofaccounting fraud.